2022
DOI: 10.1002/cne.25376
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the expression of gastrin‐releasing peptide and its receptor in the trigeminal and spinal somatosensory systems of Japanese macaque monkeys: Insight into humans

Abstract: Gastrin‐releasing peptide (GRP) and its receptor (GRPR) have been identified as itch mediators in the spinal and trigeminal somatosensory systems in rodents. In primates, there are few reports of GRP/GRPR expression or function in the spinal sensory system and virtually nothing is known in the trigeminal system. The aim of the present study was to characterize GRP and GRPR in the trigeminal and spinal somatosensory system of Japanese macaque monkeys (Macaca fuscata). cDNA encoding GRP was isolated from the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Somatosensation from the eyes is conveyed to the brain by trigeminal ganglion (TG) neurons, which terminate in the trigeminal sensory nuclei of the medulla oblongata. We have shown that one of the trigeminal sensory nuclei, the spinal trigeminal nucleus caudalis (Sp5C), contains gastrin-releasing peptide (GRP)-immunoreactive (ir) fibres of TG neurons and that the GRP receptor (GRPR) is localized to Sp5C in Asian musk shrews (Suncus murinus), mice, rats and macaque monkeys [17][18][19][20]. Because the GRP-GRPR system in the spinal somatosensory system contributes to itch sensation from the body region in mice [21][22][23][24][25][26], we hypothesize that the trigeminal GRP-GRPR system is involved in the transmission of itch from the eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Somatosensation from the eyes is conveyed to the brain by trigeminal ganglion (TG) neurons, which terminate in the trigeminal sensory nuclei of the medulla oblongata. We have shown that one of the trigeminal sensory nuclei, the spinal trigeminal nucleus caudalis (Sp5C), contains gastrin-releasing peptide (GRP)-immunoreactive (ir) fibres of TG neurons and that the GRP receptor (GRPR) is localized to Sp5C in Asian musk shrews (Suncus murinus), mice, rats and macaque monkeys [17][18][19][20]. Because the GRP-GRPR system in the spinal somatosensory system contributes to itch sensation from the body region in mice [21][22][23][24][25][26], we hypothesize that the trigeminal GRP-GRPR system is involved in the transmission of itch from the eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence for c-Fos and beta-galactosidase (β-gal), an indicator of Grpr expression was conducted according to our previously described methods ( Takanami et al, 2022 ). Non-specific binding components were blocked with 1% normal donkey serum and 1% bovine serum albumin in PBS containing 0.3% Triton X-100 for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In the spinal sensory system, gastrin-releasing peptide (GRP) and GRP receptor (GRPR) expressed in the spinal dorsal horn have been reported to specifically transmit acute and chronic itch, based on experiments using mice ( Sun and Chen, 2007 ; Sun et al, 2009 ; Zhao et al, 2013 ; Akiyama et al, 2014 ; Barry et al, 2020 ; Kiguchi et al, 2020 ; Kanehisa et al, 2022 ). In the trigeminal sensory system, we previously reported that GRP is expressed in the trigeminal ganglia and GRPR is specifically expressed in the superficial layer of the caudal part of the spinal trigeminal nucleus (Sp5C) in mice, rats, Suncus, and monkeys ( Takanami et al, 2014 , 2016 , 2022 ). However, whether GRPR in Sp5C is actually involved in the transmission of facial itching is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrin-releasing peptide (GRP) in somatosensory neurons encodes itch-specific information and can activate GRPR, a G q protein-coupled receptor (GPCR), in the spinal cord to transmit itch information in mice ( Barry et al, 2020 ; Chen, 2021 ; Sun and Chen, 2007 ; Sun et al, 2009 ). GRP is conserved across animal phyla, including mammals ( Hirooka et al, 2021 ; Takanami et al, 2022 ). Suprachiasmatic nucleus (SCN) GRP neurons are a subset of retinorecipient cells located in the ventrolateral side (the core area) and convey photic information directly from the retinohypothalamic tract (RHT) ( Abrahamson and Moore, 2001 ; Karatsoreos et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%